Functional analysis of the 5- regulatory region of the 5-aminolevulinate synthase (alas1) gene in response to estrogen - Du Plessis, N; Kimberg, M; Zaahl, M G; Sadie, A; Venter, M; Van Der Merwe, L; Louw, A; Warnich, L (Cellular and Molecular Biology, 2009)
Genetic defects in the heme synthesis enzymes lead to a group of heterogeneous disorders termed the porphyrias. Numerous factors influence the clinical expression of porphyrias, primarily by altering the rate of heme synthesis. To date, no genotype-phenotype correlation has been made to explain the variable penetrance observed in variegate porphyria (VP) and other acute hepatic porphyrias. As first and rate determining gene in the heme pathway, 5-aminolevulinate synthase-1 (ALAS1), appears to be an ideal candidate modifier. Previous studies established critical mechanisms for ALAS1 regulation and a direct transcriptional response to drugs by defined drug-responsive enhancer sequences (ADRES). To identify possible functional variants within the 5’ region of ALAS1, selected regulatory regions, including the ADRES elements, were screened by DNA sequencing analysis in 26 VP patients heterozygous for the causative R59W mutation in the protoporphyrinogen oxidase (PPOX) gene. Two novel variants, -853C>T and -1253T>A were identified. In silico analyses indicated that the -853C>T transition is located immediately 5’ to a half-palindromic putative estrogen receptor binding site. Co-transfection experiments with an estrogen receptor-Î± (ERÎ±) expression vector in HepG2 cells, suggest that this region mediates an increased transcriptional response in the presence of estrogen (E2) and ERÎ±. The wild-type -853C/-1253T allele induced a 47% increase in transcription, while the -853T/-1253A double mutant allele showed a 35% increase in transcription compared to expression in the absence of E2. The highest induction was observed for the mutant -853T/1253T allele that generated an increase of 66%. We conclude that the -853T variant functions as an enhancer in the presence of estrogen and speculates that the -1253A variant reduces transcription activity.